Read before you buy - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Ten crop protection publications of CABI Publishing can be read on the Internet until 1 May 1999. CABI thus enables users to view the full content of the new titles on the Internet before buying the books. Titles cover the following topics:...